Construction of a technological platform to improve communication among educational stakeholders - Ramos Chavira, Lorena Carolina (2015)
This research sought to study the communication conditions in an educational institute with the purpose of knowing the effectiveness of the communicational interchanges between the parts involved and with the purpose of designing a tool to improve the communication between students, teachers, principals and parents. The efficiency of the communication was analyzed, as well as the benefits they obtain from it. The qualitative method was used to obtain their opinion through interviews. The collected information was used to design a technological platform that would allow keeping communication, taking into account the needs of the school under study. It is concluded that the communication is efficient between the internal actors but deficient with the external participants, for which the use of a technological platform of communication would benefit the process.